Survival and drug persistence in patients receiving inhaled treprostinil at doses greater than 54 µg (nine breaths) four times daily. (1st October 2021) - Shapiro, Shelley; Mandras, Stacy; Restrepo‐Jaramillo, Ricardo; Shen, Eric; Broderick, Meredith; Rao, Youlan; Lee, Dasom; Nelsen, Andrew C.
Abstract : Treprostinil is a prostacyclin approved for the treatment of pulmonary arterial hypertension. Commercial data sets indicate that approximately 20–25% of patients are prescribed a higher dose than the maximum recommended dosage of nine breaths per treatment session (bps) (54 μg), four times a day (QID) and numerous studies have demonstrated the safety of doses >9 bps QID. This phase 4, retrospective analysis of specialty pharmacy records assessed the effects of inhaled treprostinil at doses >9 bps QID. Patients receiving inhaled treprostinil between September 2009 and June 2018 were included, and a random sampling of 5000 patients was selected for further analysis. Subjects were grouped based on the highest dose reached for ≥2 months within a rolling six‐month window and were followed for up to three years. Of the total of 5000 patients analyzed, 28.5% received >9 bps QID. Survival rates were significantly higher in the >9 bps QID dosing group for years one, two, and three ( P < 0.001). The time to transition to parenteral therapy was significantly longer for those at doses >9 bps (17.5 months) compared to doses ≤9 bps (9.5 moths; P < 0.0001). Drug persistence was also significantly higher for those taking >9 bps at years 1, 2, and 3 ( P < 0.0001). Patients receiving inhaled treprostinil at doses >9 bps QID had a higher rate of survival and drug persistence over a three‐year period, suggesting that higher doses may provide clinically relevant benefits while remaining tolerable.